THE PARTIDO DOS TRABALHADORES: elements for analysis, from the formation to the coup of 2016 - Giugliano, Rogério Gimenes; de Novion, Jacques (Universidade de Brasília, 2018)
From the debates established at the seminar "The Left in the Present: Dialogues Latin America and Europe", held at the University of Brasília in October 2017, this text presents elements for analysis on the Workers' Party in Brazil.